Religion Today: Tradition, Modernity and Change : Global Religious Movements in Regional Context - Edited by Wolffe, John (Aldershot Ashgate, 2002)
This series offers an in-depth introduction to contemporary themes and challenges in religious studies. The contents highlight the central issues and ideas that are shaping religion today - and will continue to do so tomorrow
Include Illustration and Index
Keywords: Religions